Factors Affecting with Not Receiving Cervical Cancer Screening Test among the First-Degree Relatives of Cervical Cancer Risk Group in Mueang District, Mahasarakham Province - Nithisabsakul, Nithipa; Kamsa-ard, Supot; Mithala, Sarawut; Teemueangsai, Wisaruda (Srinagarind Medical Journal, 2022)
Background and Objective: Cervical cancer in the first-degree relatives of cervical cancer risk group still have to low attendance to screening tests and less study. The objectives of this study were to determined factors affecting with not receiving cervical cancer screening among the first-degree relatives of cervical cancer risk group in Mueang district, Mahasarakham Province. Methods: This study was a case-control study among the first-degree relatives of cervical cancer risk group in Mueang district, Mahasarakham Province. A total were 246 Cases, Cases were 123 women who never had cervical cancer screening, and Controls were 123 woman who did received cervical cancer screening. Multiple logistic regression was used, presenting with adjusted odds ratio (Adjusted OR) with their 95% Confidence interval (95%CI) Result: The results showed factors affecting with not receiving cervical cancer screening among the first-degree relatives of cervical cancer risk group were education level (Adjusted OR = 0.72; 95%CI = 0.53-0.98), income (Adjusted OR = 2.29; 95%CI = 1.28-4.07), first experience of sexual intercourse (Adjusted OR = 3.19; 95%CI = 1.79-5.68), having received support from family (Adjusted OR = 0.19; 95%CI = 0.08-0.45), and having received of information about cervical cancer screening (Adjusted OR = 3.59; 95%CI = 1.38-9.29) Conclusion: The finding showed that education level, income, first experience of sexual intercourse, having received support from family and having received of information about cervical cancer screening related to with not receiving cervical cancer screening among the first-degree relatives of cervical cancer risk group.